Improved gravitational search algorithm for proportional integral derivative controller tuning in process control system [electronic resource] - Mohamad Saiful Islam Aziz, 1989-; Sophan Wahyudi Nawawi, supervisor; Shahdan Sudin; Norhaliza Abdul Wahab, supervisor 455420; Fakulti Kejuruteraan Elektrik 540663 (2016)
Thesis (Sarjana Sains (Elektrikal)) - Universiti Teknologi Malaysia, 2016